2022
DOI: 10.1186/s13041-022-00987-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute social defeat stress activated neurons project to the claustrum and basolateral amygdala

Abstract: We recently reported that a neuronal population in the claustrum (CLA) identified under exposure to psychological stressors plays a key role in stress response processing. Upon stress exposure, the main inputs to the CLA come from the basolateral amygdala (BLA); however, the upstream brain regions that potentially regulate both the CLA and BLA during stressful experiences remain unclear. Here by combining activity-dependent viral retrograde labeling with whole brain imaging, we analyzed neurons projecting to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Interestingly, the CI and BLA have multiple common upstream areas. Neurons that project to both regions may coordinate their activity in response to a psychological stressor (Tanuma et al., 2022). The hippocampus, as part of the limbic system of the brain, plays an important role in long‐term memory and spatial navigation (Cossart & Khazipov, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the CI and BLA have multiple common upstream areas. Neurons that project to both regions may coordinate their activity in response to a psychological stressor (Tanuma et al., 2022). The hippocampus, as part of the limbic system of the brain, plays an important role in long‐term memory and spatial navigation (Cossart & Khazipov, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The claustrum (CL) has extensive connections with multiple cortical and subcortical brain regions, including the PFC and amygdala (Jackson et al 2018; Smith et al 2020). Although possible CL involvement in social behavior modulation as well as in ethanol effects has not been studied in laboratory rodents, a subpopulation of CL neurons has been shown to modulate stress-induced anxiety-like behavior of male mice through interaction with the BLA (Niu et al 2022; Tanuma et al 2022). However, an important issue of CL involvement in regulation of social interaction and/or anxiety in adolescent rats of both sexes under basal conditions as well as following ethanol challenge still needs to be addressed in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacogenetic inhibition of the CLA-Prelimbic cortex circuit during contextual fear conditioning attenuated recent fear retrieval (30). Other studies also showed that stress and footshock could activate the CLA (25,(31)(32)(33). However, the role of the CLA in fear encoding and anxiety disorders remains largely understudied.…”
mentioning
confidence: 99%